Perbandingan Kejadian Post Dural Puncture Headache pada Pasien Seksio Sesarea dengan Anestesi Spinal Menggunakan Teknik Median dan Paramedian - , Rizki; , Suwarman; Bisri, Tatang (Perdatin Pusat, 2014)
spinal (LCS) berpengaruh terhadap timbulnya PDPH. Berbagai faktor yang memengaruhi insidensi kejadian PDPH, meliputi jenis kelamin, usia, kehamilan, riwayat PDPH sebelumnya, ukuran dan bentuk jarum, arah jarum, jumlah percobaan tusukan, teknik penusukan median atau paramedian, dan keahlian ahli anestesi. Tujuan penelitian adalah membandingkan kejadian PDPH wanita hamil yang dilakukan seksio sesarea dengan anestesi spinal menggunakan teknik median dan paramedian di RS Dr. Hasan Sadikin Bandung, periode Maret–April 2014. Penelitian ini dilakukan secara uji klinis acak terkontrol tersamar tunggal terhadap 44 pasien wanita hamil aterm dengan status fisik American Society of Anesthesiologists (ASA) I dan II yang menjalani seksio sesarea dengan anestesi spinal. Subjek dibagi menjadi dua, kelompok paramedian (P) dan kelompok median (M). Kelompok P dilakukan penusukan menggunakan teknik paramedian dan kelompok M menggunakan teknik median dengan m jarum spinal ukuran 25-gauge tipe Quincke. Data hasil penelitian dianalisis menggunakan metode chi-kuadrat Hasil penelitian menunjukkan tidak ada perbedaan yang bermakna pada kedua kelompok (p=0,351), terdapat 2 kejadian (9%) PDPH pada kelompok median (n=22) dan tidak ditemukan kejadian pada kelompok paramedian (n=22). Simpulan penelitian ini adalah tidak ada pengaruh teknik penusukan menggunakan teknik paramedian atau median terhadap kejadian PDPH pada wanita hamil yang dilakukan seksio sesarea Kata kunci: Anestesi spinal, teknik paramedian, post dural puncture headache, teknik median Post dural puncture headache (PDPH) is an iatrogenic complication of spinal anesthesia. Cerebro spinal fluid (LCS) leak have effect on the incidence of PDPH. Various factors affect the incidence of PDPH include gender, age, pregnancy, history of previous PDPH, the size and shape of the needle, the needle direction, the number of attempted punctures, median or paramedian puncture technique, and skill of the operator. The purpose of this study was to compare the incidence of PDPH in pregnant women who performed caesarean section under spinal anesthesia using median and paramedian techniques in Dr. Hasan Sadikin Hospital Bandung at April-May 2014. This research was conducted in single-blind randomized controlled clinical trial on 44 at term pregnant women with American Society of Anesthesiologists (ASA) physical status I and II undergoing cesarean section with spinal anesthesia. Subjects were divided into two groups paramedian (P) and the median (M). Group P performed using paramedian puncture technique and M groups using the median technique. Both of technique using a 25- gauge Quincke needle. The data were analyzed using chi-square method The results of this study showed no significant difference in both groups (p=0.351) , with 2 incidences of PDPH (9 % ) in the group median (n=22) and not found in the paramedian group (n=22). Conclusions there is no difference between median and paramedian techniques on the incidence of PDPH in pregnant women who performed caesarean section. Key words: Median, paramedian, post dural puncture headache, spinal anesthesia Reference Paech MJ, Whybrow T. The prevention of anaesthesiology. Asean J Anaesth.2007;8:86–95. Amorim JA, Gomes de Barros MV, Valenca MM. Post-dural (post-lumbar) puncture headache: risk factors and clinical features. Cephalalgia. 2012 Sep;32(12):916−23. Singh J, Ranjit S, Shrestha S, Limbu T, Marahatta SB. Post dural puncture headache. J Inst Med. 2010;32(2):30−2. Mosaffa FK, Madadi F, Khoshnevis SH, Besheli LD, Eajazi A. Post-dural puncture headache: a comparison between median and paramedian approaches in orthopedic patients. Anesth Pain. 2011;1(2):66–9. Wu CL, Christo P, Richman JM, Hsu W. Postdural puncture headache: an overview. Int J Pain Med Pall Care. 2004;3(2):53–9. Turnbull DK, Shepherd DB. Postdural puncture headache: pathogenesis, prevention and treatment. Br J Anaesth. 2003 Nov;91(5):718−29. Ghaleb A, Khorasani A, Mangar D. Postdural puncture headache. Intern J General Med. 2012;5:45–51 Vallejo MC, Mandell GL, Sabo DP, Ramanathan S. Postdural puncture headache: a randomized comparison of five spinal needle in obstetric patients. Anesth Analg. 2000;91:916−20. Lybecker H, Moller JT, May O, Nielsen HK. Incidence and prediction of post dural puncture headache: a prospective study of 1021 anesthesia. Anesth Analg. 1990;70:389–94. Haider SZ, Aziz MA., Qasim M. Post dural puncture headache - a comparison of midlineand paramedian approaches. Biomedica. 2005;21:90−2. Valenca MM, Amorim JA, Moura TP. Why don't all individuals who undergo dura mater/arachnoid puncture develop postdural puncture headache? Anesth Pain. 2012;1(3):207–9. Choi PT, Galinski SE, Takeuchi L, Lucas S, Tamayo C, Jadad AR. PDPH is a common complication of neuraxial blockade in parturients: a meta-analysis of obstetrical studies. Canadian J Anesth. 2003;50(5):460–9. Jabbari A, Alijampour E, Mir M, Hashem NB, Rabiea SM, Rupani MA. Post spinal puncture headache, an old problem and new concepts: review of articles about predisposing factors. Caspian J Intern Med. 2013;4(1):595–602. Kempen P, Mocek C. Bevel direction, dura geometry, and hole size in membrane puncture: laboratory report. Reg Anesth. 1997;22(3):267–72. Fink BR, Walker S. Orientation of fibers in human dorsal lumbar dura mater in relation to lumbar puncture. Anesth Analg. 1989 Dec;69(6):768–72. Hatfalvi B. Postulated mechanisms for postdural puncture headache and review of laboratory models. Clinical experience. Reg Anesth. 1995;20(4):329−36.